2018
DOI: 10.1080/07357907.2018.1430812
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Lacking E1b Efficiently Induces Cytopathic Effect in HPV-16-Positive Murine Cancer Cells via Virus Replication and Apoptosis

Abstract: Conditionally replicative adenoviruses (CRAds) replicate poorly in murine cancer cells; however, E1b-deleted CRAds may replicate effectively in HPV16-E6/E7-positive murine cancer cells (TC-1). The HPV16 E7 open reading frame encodes functions analogous to these deleted adenovirus E1 proteins. In this study, an E1b-deleted CRAd (Adhz60) was evaluated for its ability to replicate and induce oncolysis in TC-1 cells. Adhz60-mediated oncolysis was similar in TC-1 and HeLa cells. Productive viral replication was evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is still unclear why human adenovirus cannot replicate e ciently in murine cells. Martinez et al reported E1b-deleted conditionally replicative adenoviruses may replicate effectively in HPV16-E6/E7-positive murine cancer cells (TC-1) [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear why human adenovirus cannot replicate e ciently in murine cells. Martinez et al reported E1b-deleted conditionally replicative adenoviruses may replicate effectively in HPV16-E6/E7-positive murine cancer cells (TC-1) [22].…”
Section: Discussionmentioning
confidence: 99%